2018
DOI: 10.1101/456921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A High-Resolution Luminescent Assay for Rapid and Continuous Monitoring of Protein Translocation Across Biological Membranes

Abstract: Abbreviations:AA -antimycin A; IMM -inner mitochondrial membrane; mt-11S -mitochondrial-targeted 11S; H6 11S -Nterminal 6xHis tagged version of 11S; OMM -outer mitochondrial membrane; OVA -oligomycin, valinomycin and antimycin A (full depolarisation cocktail); MTS -mitochondrial targeting sequence, NanoBiT -NanoLuc Binary Technology; PAM -presequence-translocase-associated import-motor; pep86high-affinity version of NanoBiT small fragment; pep114 -small fragment of NanoBiT; PMF -proton motive force; TIM -trans… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…Using NanoLuc to Dissect Translocation Kinetics. To interrogate the kinetics of protein transport in sufficient detail to reveal mechanistic information, we used the recently developed NanoLuc system (16). In essence, NanoLuc luciferase missing a single β-strand (11S) is encapsulated within proteoliposomes (PLs) incorporating the Sec machinery, while a high-affinity version of the missing β-strand (Pep86) is fused to a translocation substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using NanoLuc to Dissect Translocation Kinetics. To interrogate the kinetics of protein transport in sufficient detail to reveal mechanistic information, we used the recently developed NanoLuc system (16). In essence, NanoLuc luciferase missing a single β-strand (11S) is encapsulated within proteoliposomes (PLs) incorporating the Sec machinery, while a high-affinity version of the missing β-strand (Pep86) is fused to a translocation substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Very precise measurements of protein transport are required to distinguish between these types of mechanisms, such as those produced by the recently published NanoLuc transport assay (16). Here, we extend the use of the NanoLuc assay to reveal the elementary steps of the ATP-driven protein transport mechanism, using the model preprotein prospheroplast protein Y (pSpy).…”
mentioning
confidence: 99%
“…To analyze translocation kinetics at high time resolution, we utilized a recently described assay 33 that continuously follows the reaction progress in real-time through light emission by the NanoLuc luciferase. NanoLuc can be split into two asymmetric fragments p86 (11 amino acids) and 11S (159 amino acids), neither of which has significant enzymatic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The codon optimized 11S sequence was obtained as a synthetic DNA fragment (IDT DNA) and cloned into a His-SUMO backbone (Addgene Plasmid #37507) for expression. The coding sequence for the p86 “dark” peptide (VSGWALFKKIS) 33 was inserted into a plasmid encoding glutathione S transferase (GST) to generate a C-terminal fusion in the same backbone and termed “GST-dark.” For expression, plasmids were transformed into BL21(DE3) cells. Expression was induced with a final concentration of 0.2% arabinose at 37 °C when the OD600 reached 0.4–0.6.…”
Section: Methodsmentioning
confidence: 99%
“…Since the NanoLuc reaction follows a Michaelis–Menten kinetics (Hall et al, ), use of this assay does even allow estimating the actual concentration of secreted or injected proteins. The herein described set‐up has been successfully used for assessing the function of the Yersinia T3SS (Lindner, Milne‐Davies, Langenfeld, & Diepold, ) and it was shown that a similar set‐up also works for monitoring secretion through the Sec‐translocon (Pereira et al, ). Thus, NLuc fusions have a high potential to also enable the functional analysis of other bacterial secretion systems in the future.…”
Section: Discussionmentioning
confidence: 99%